Development of a Laravel-based Publication, Research and Community Service Information System - Funny Farady Coastera; Eko Risdianto (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
The need for accurate data is really needed when departments or faculties are to be accredited, and to map lecturers who will have the opportunity in the following semester to carry out research or community service. Due to differences in data held by departments, faculties, or data at the LPPM (Institute for Research and Community Service), different data can occur due to lack of discipline in lecturers who have carried out research and service to collect reports to departments, faculties, or to LPPM. To facilitate reporting of research and community service activities by lecturers to the Department and to management, an information system is needed that can improve research and community service performance. The system development method used in this research is the SDLC (System Development Life Cycle) method. The SDLC method uses a system approach called the waterfall approach, which uses system development stages, namely requirements analysis, design, coding, system testing and support stages (maintenance), using the PHP programming language and MySQL database. The research results show that the information system developed makes it easier to manage and organize data from lecturers' research, service and publications and can help lecturers, departments and faculty leaders in obtaining the information they need online and in real time. It can be concluded that the Prisma Information System fully supports the submission of service research proposals, a faster and easier process, safer data and guaranteed credibility, dynamic configurability, more responsive design, and assistance documentation, as well as other new features.